Does Funding Impact Our Research? Causality, Normativity, and Diversity in 40 Years of U.S. Sociology of Religion. Issue 3 (10th August 2018) - May, Matthew; Smilde, David
Abstract: In this article we use a sample of 40 years of sociology journal articles (N = 1, 024) on religion to ask what role funding plays in some of the leading trends in the subdiscipline. Our analysis reveals a considerable increase in the number of published articles on religion with funding over the past 40 years as well as a shift away from public funding as the primary source of funding. Engaging our findings in previous analyses of this database, we surprisingly find a positive correlation between public funding and positive socio‐evaluative findings in articles on religion, but not between private funding and positive socio‐evaluative findings. We also find a positive correlation between funding from religious organizations and research on religion in the United States and a weak, but negative, correlation between funding from religious organizations and research on non‐Christian religious traditions. We do not find a relationship between funding and causal order.